2015
DOI: 10.4103/0974-620x.149867
|View full text |Cite
|
Sign up to set email alerts
|

A rare presentation of pigmented paravenous retinochoroidal atrophy

Abstract: A 21-year-old female patient presented with gradual progressive loss of vision in both eyes of 12 years duration. Funduscopic examination revealed bone-spicule pigmentation and choroidal and retinal pigment epithelium atrophy along the vascular arcades, with macular involvement in both eyes. The patient was diagnosed with pigmented paravenous retinochoroidal atrophy which is rare disease, uncommon in females, more commonly affecting the paravascular fundus. Very few cases of macular involvement have been repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
(11 reference statements)
0
4
1
Order By: Relevance
“…In contrast, Ahmed et al, showed a thickened cystic retinal nerve fibre layer on SD-OCT in a 79 years old woman with uniocular PPCRA which they believed supported a vascular aetiology rather than an RPE based cause. 33 We found no such changes in our series.…”
Section: Discussioncontrasting
confidence: 50%
“…In contrast, Ahmed et al, showed a thickened cystic retinal nerve fibre layer on SD-OCT in a 79 years old woman with uniocular PPCRA which they believed supported a vascular aetiology rather than an RPE based cause. 33 We found no such changes in our series.…”
Section: Discussioncontrasting
confidence: 50%
“…Pigmented paravenous retinochoroidal atrophy (PPRCA) is an unusual retinal degeneration characterized by perivenous aggregations of pigment clumps associated with peripapillary and radial zones of retinochoroidal atrophy that are distributed along the retinal veins [ 1 ]. Patients are often asymptomatic and the diagnosis is based on a characteristic fundus appearance [ 2 ]. The etiology remains unknown or idiopathic, although many report of familial cases make hereditary nature of this condition quite apparent [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…3 The involvement of the macula is an important factor that may aggravate the disease, leading to severe visual impairment. 1,28 In a prior study, chorioretinal atrophy affecting the fovea was found to be present in only a small proportion of patients. 1,29 On optical coherence tomography (OCT) images, macular involvement is usually seen as extensive damage of the outer retina and RPE.…”
Section: Associated Ocular Findingsmentioning
confidence: 95%
“…1 With this technique, other macular comorbidities have been reported, such as epiretinal membrane, cystoid macular edema, lamellar and full-thickness macular hole, RPE atrophy and macular coloboma. 5,28,30,36,57 OCT of the affected paravenous regions show variable degree of outer retinal layers thinning, focal or generalized choroidal thinning and RPE atrophic changes, together with areas of pigment clumping visible as intraretinal hyperreflective plaques with posterior hypotransmission. 1,8 In particular, areas characterized by a reduction of the outer retinal thickness without RPE atrophy correspond to the junctional zones in FAF.…”
Section: Optical Coherence Tomographymentioning
confidence: 99%
See 1 more Smart Citation